2001
DOI: 10.1002/1097-0320(20011201)45:4<237::aid-cyto10024>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a decrease in green fluorescent protein fluorescence for the monitoring of cell death: An assay amenable to high-throughput screening technologies

Abstract: Objective To identify genes that may participate in the pathophysiology of Sjögren's syndrome (SS), the technique of differential display was applied to labial minor salivary gland (MSG) biopsy samples. Methods Total RNA was isolated from MSG biopsy samples from a woman with primary SS and a control subject, and the differential display protocol with 8 different random oligonucleotide primers was performed. One particular differentially expressed fragment showed 98% homology with the cysteine‐rich secretory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
53
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 53 publications
7
53
0
Order By: Relevance
“…Erb and colleagues (17) recently showed that the loss of GFP is a sensitive and specific marker of different types of death in some nonneuronal cell types. If GFP loss corresponds to the death of a neuron, it can be quantified over time as a measure of neuronal survival (17,18). To test this possibility, we simultaneously measured the loss of GFP in transfected neurons and the loss of membrane integrity by using a membrane-impermeant nuclear dye, EtHD.…”
Section: Automated Longitudinal Analysis Of Biological Processessupporting
confidence: 62%
See 1 more Smart Citation
“…Erb and colleagues (17) recently showed that the loss of GFP is a sensitive and specific marker of different types of death in some nonneuronal cell types. If GFP loss corresponds to the death of a neuron, it can be quantified over time as a measure of neuronal survival (17,18). To test this possibility, we simultaneously measured the loss of GFP in transfected neurons and the loss of membrane integrity by using a membrane-impermeant nuclear dye, EtHD.…”
Section: Automated Longitudinal Analysis Of Biological Processessupporting
confidence: 62%
“…Next, we tested whether the expression of GFP affected survival. Studies of the potential toxicity of GFP and its variants have arrived at conflicting conclusions (17)(18)(19)21). If GFP is toxic, the level of GFP expression as measured by GFP fluorescence should correlate inversely with duration of survival.…”
Section: Automated Longitudinal Analysis Of Biological Processesmentioning
confidence: 95%
“…Optical imaging of GFP-expressing cancer cells offers a means of visualizing tumors in situ in whole intact animals (16,17), and we reasoned that combining the 5TGM1 myeloma model with GFP imaging would facilitate accurate monitoring of myeloma tumors disseminated throughout the skeleton. This capability is especially important in settings where the model is being used to predict efficacy of antitumor agents, as there is a marked decrease in emitted fluorescence observed following death induction in cells expressing eGFP (20).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, visualization of emitted fluorescence requires no preparative procedures, substrates, or contrast agents, and it is convenient and relatively inexpensive. Moreover, 5TGM1-eGFP myeloma cells could be used to develop high-throughput GFP-based microplate cytotoxicity screens for evaluation of novel anticancer agents, as shown for other eGFP-expressing tumor-derived cells (20). In vivo efficacy of positive ''hits'' could then be rapidly determined in mice inoculated with the same 5TGM1-eGFP cells as we have shown in this report.…”
Section: Resultsmentioning
confidence: 99%
“…However, all of these assays employ FACS to assess drug activity and as such are limited in the number of compounds that can be tested during a given time period. Combining GFP with a microtiter format enhances the throughput of the screening system considerably and has recently been applied to determine the activities of anticancer drugs (37,47), but to our knowledge it has not as yet been applied for antimicrobial drug screens.…”
mentioning
confidence: 99%